2006
DOI: 10.1381/096089206775565276
|View full text |Cite
|
Sign up to set email alerts
|

Does Gastric Dilatation Limit the Success of Sleeve Gastrectomy as a Sole Operation for Morbid Obesity?

Abstract: LSG has been highly effective for weight reduction for morbid obesity even as the sole bariatric operation. Gastric dilatation was found in only 1 patient in this short-term follow-up. Weight regain following LSG may require conversion to RYGBP or DS. Follow-up will be necessary to evaluate long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
106
1
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(127 citation statements)
references
References 42 publications
11
106
1
7
Order By: Relevance
“…In human beings, the failure of weight lost after SG has been explained by the dilatation of the stomach. Langer has observed gastric dilatation with contrast-enhanced upper GIS series in one patient, and weight gain after weight lost in 3 out of 23 patients in 12 months [22]. In rats, postmortem examinations revealed that the dilation of resected gastric tissue reached nearly normal size, and dilatation of remnant gastric tissue in SG has been also observed in our study (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…In human beings, the failure of weight lost after SG has been explained by the dilatation of the stomach. Langer has observed gastric dilatation with contrast-enhanced upper GIS series in one patient, and weight gain after weight lost in 3 out of 23 patients in 12 months [22]. In rats, postmortem examinations revealed that the dilation of resected gastric tissue reached nearly normal size, and dilatation of remnant gastric tissue in SG has been also observed in our study (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…The surgical complications most commonly encountered are: fistula, which usually occurs at the angle Table 2 Table 2 Table 2 Table 2 Table 2 Table 3 Table 3 Table 3 Table 3 Table 3 Table 4 Table 4 Table 4 Table 4 Table 4 Distribution of patients according to the quality of life after treatment. of Hiss, is difficult to treat, with an incidence ranging from 0.7 to 5.3% 14,17 ; stenosis, especially in the angular notch, due to failure when preparing the gastric tube 27 ; portals infection; hernia; cholelithiasis 3.8% 15; gastroesophageal reflux disease 28,29 ; and dilatation of the gastric pouch after two years of operation and weight regain 15,28,30,31 . The reduction of the stomach promotes reduced food intake and reduced parietal cells, resulting in decreased production of hydrochloric acid, which is important in the absorption of iron.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Among the causes of regained weight we can highlight two main technical mistakes while performing the operation: use of catheters with diameter greater than 32 Fr. to calibrate the stomach and no resecting the antral region, initiating the gastroplasty at the great gastric curvature more than six cm from the pylorus 20,25,30,31 . We understand that the approach to obesity should not just be restricted to surgical treatment.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Given the effectiveness of LSG in super-super-obese and super-obese patients, Langer et al [40] reported the results of LSG in morbidly obese patients. A total of 23 patients (8 super-obese and 15 with a BMI < 50 kg/m ) were included in the prospective study.…”
Section: Weight-loss Outcomesmentioning
confidence: 99%